Efficient circuit topologies for inductive power transfer - Nguyen, Xuan Bac (2016)
In recent years, inductive power transfer (IPT) systems have gained much attention, interest and development. IPT systems are found to be having numerous advantages over conventional wired power systems in relation to convenience, safety, isolation, operation in hostile conditions and flexibility and have proven its worth in many applications such as electric vehicle charging systems, lighting, material handling, grid-tied PV inverters, etc. A typical IPT system employs a primary power converter to generate high frequency current into one or more inductive tracks/coils in the primary side and then magnetically coupled to one or more power pick-ups in the secondary side. Development of efficient IPT systems has been receiving increased attention and many attempts have recently been made to improve the overall efficiency. The overall efficiency of an IPT system largely depends on the losses that incur in coupling coils and converters. This thesis focuses on the development of power converters and modulation strategies for IPT systems to minimize the power losses and improve the power transmission capability. In case of power converters, the power losses consist of conduction losses and switching losses of switching devices. In order to reduce these power losses, the power converters should either have reduced number of power switches and power stages or efficient commutation strategies. In the case of the coupling coil losses, it can be minimized by either with the use of proper magnetic circuit and coil winding design or an appropriate modulation strategy. Towards that end, certain techniques are proposed to develop power converters and control algorithms with optimized overall efficiency for IPT systems. Firstly, in order to give the reader sufficient knowledge to comprehend the proposed power converters and modulation strategies that will be discussed in this thesis, chapter 2 will present an overview of IPT circuit topologies. Fundamental components of IPT systems will be briefly introduced first. Thereafter, a review of IPT power converters together with switching methods will be presented. Secondly, a novel direct AC-AC matrix converter topology is proposed to generate a high frequency current with a reduced number of semiconductor switches. The proposed topology transforms 50-Hz 3-phase utility supply to a single-phase high frequency supply which in turn can be used to directly excite the primary side resonant network of an IPT system. With the reduction of number of conversion stages, switching and conduction losses can be reduced. A mathematical model for the proposed system has also been presented with simulation and experimental results to demonstrate the feasibility of the proposed topology. The power loss evaluation of the proposed converter as well as of the conventional IPT converter demonstrated the benefits of the proposed system. Thirdly, an optimized phase shift modulation strategy has been proposed to minimize coil losses of bidirectional IPT (BIPT) systems. Moreover, a comprehensive study on the impact of system parameters on the overall efficiency has been carrried out. The analyses and simulation results provide the conditions for obtaining the maximum overall efficiency. A closed loop controller has been proposed to operate the system with optimized effficiency. Experimental results demonstrate the feasibility of the proposed concept. Fourthly, multilevel converters including cascaded multilevel converters, diode clamped multilevel converters, capacitor clamped multilevel converters and other advanced multilevel converter topologies with reduced number of power switches are introduced for BIPT systems together with proposed modulation strategies to minimize the power losses of switching devices. The presented power converters can be used in low to high powered applications. Cascaded multilevel converters are suitable in the case of several individual DC sources such as PV cells are connected while diode clamped multilevel converters and capacitor clamped multilevel converters are suitable in the case of high voltage power supply. Multilevel converters with reduced number of power switches are employed to lower switching losses and conduction losses of IPT systems.